Seaweed (Gracilariopsis funicularis) biochar incorporation into a goat manure–food waste vermicompost for optimized vermidegradation and nutrient release - Katakula, Asteria Aili Ndiipohamba; Gawanab, Werner; Handura, Bethold; Itanna, Fisseha; Mupambwa, Hupenyu Allan (Frontiers in Sustainable Food Systems, 2022)
Vermicomposts are organic fertilizer sources that are being promoted; however, their concentrations of macronutrients such as NPK are very low. This study, therefore, evaluated the effects of amending goat manure–food waste mixture with biochar prepared from seaweed (Gracilariopsis funicularis) at 0% (control), 2, 4, 6, and 8% on vermicompost degradation and macronutrient release. After 10 weeks of vermicomposting, the highest pH of 9.06 was observed within the control, whilst the lowest was 8.7 in the 8% treatment. The electrical conductivity showed a positive relationship with the level of biochar incorporation with the highest of 16.5 mS/cm from the 8% treatment, whilst the lowest was within the control with 6 mS/cm. There were no significant differences between treatments on humification parameters; however, there were significant differences in the changes in a C/N ratio with the final C/N ratio of 14.4, 14.9, 16.7, 15.1, and 14.4 for the control, 2, 4, 6, and 8% treatments, respectively. A higher incorporation rate resulted in the higher concentration of potassium with a value of 32.3 g/kg at week 8. The final percentage change in Olsen P was 19, 14.2, 7.3, 4.1, and 3.0% for the 8%, 6%, control, 4%, and 2% treatments, respectively. An optimized level of 6% to 8% biochar incorporation ratio can be recommended. However, the incorporation of G. funicularis biochar does not seem to influence changes in the vermidegradation efficiency, though it can significantly improve the macronutrients such as P, K, and Mg concentrations as well as the macroelement concentrations.